The impact of political ideology, knowledge and participation on electoral conspiracy endorsement - Jiang, Yanru (Frontiers in Political Science, 2023)
From voting fraud to Russian interference, electoral conspiracy theories have circulated on social media since the 2016 presidential election with alarming magnitude. Previous conspiracy studies have primarily focused on psychological causes that contribute to the conspiracy mentality, and the discussion on political antecedents of conspiracy endorsement remains lacking. This study selects popular conspiracies reflecting various political ideologies and conducts multiple survey rounds (n = 500) to compare and contrast the effect of partisan affiliations on conspiracy endorsement. Drawing from the extant literature from psychology, communication, and political science and using two-way and three-way interaction models, this study examines three political antecedents—political ideology, knowledge, and participation— and their interactive effects on conspiracy endorsement. The results indicate that individuals with higher levels of political affiliation and knowledge illustrate stronger conspiracy endorsement, and this effect is stronger for conservatives than liberals. Additionally, increased political participation reduces the endorsement of conservative conspiracies and heightens the endorsement of liberal ones among both conservatives and liberals.